2021
DOI: 10.1108/ijlm-11-2020-0448
|View full text |Cite
|
Sign up to set email alerts
|

Lean resilience: AURA (Active Usage of Resilience Assets) framework for post-COVID-19 supply chain management

Abstract: PurposeSupply chain resilience capabilities are usually considered in light of some anticipated events and are as passive assets, which are “waiting” for use in case of an emergency. This, however, can be inefficient. Moreover, the current COVID-19 pandemic has revealed difficulties in the timely deployments of resilience assets and their utilization for value creation. We present a framework that consolidates different angles of efficient resilience and renders utilization of resilience capabilities for creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(142 citation statements)
references
References 92 publications
6
134
0
2
Order By: Relevance
“…However many organizations were not prepared for the practicalities of fulfilling online orders, and planning processes were ill-equipped to respond to the sudden increase in demand as a consequence of Covid-19. For many supply chains it therefore rapidly became apparent that an increased level of supply chain resilience was required (Ivanov, 2021;Queiroz et al, 2020;van Hoek, 2020). Developing supply chain resilience in response to disruption poses challenges; on the one hand there is large amount of uncertainty and on the other a significant amount of data is generated (Wamba et al, 2020c).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However many organizations were not prepared for the practicalities of fulfilling online orders, and planning processes were ill-equipped to respond to the sudden increase in demand as a consequence of Covid-19. For many supply chains it therefore rapidly became apparent that an increased level of supply chain resilience was required (Ivanov, 2021;Queiroz et al, 2020;van Hoek, 2020). Developing supply chain resilience in response to disruption poses challenges; on the one hand there is large amount of uncertainty and on the other a significant amount of data is generated (Wamba et al, 2020c).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Developing supply chain resilience in response to disruption poses challenges; on the one hand there is large amount of uncertainty and on the other a significant amount of data is generated (Wamba et al, 2020c). Hence, due to uncertainty and vast data it becomes very difficult for supply chains to achieve their desired degree of resilience (Ivanov, 2021). In consequence, many firms are making short term predictions and focusing on strengthening their supply chain capabilities (Sundarakani et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the spectral emissivity analysis of corn canopy in different growth periods has been carried out using spectral analysis techniques, and the trend of reflectivity changes in the visible and near-infrared regions at different growth periods of maize is pointed out [18]. It gradually increases in the visible light range and gradually decreases in the near-infrared region [19]. Some scholars are doing nitrogen difference gradient experiments for different wheat varieties, showing that the differential spectrum of the canopy changes regularly with the increase in nitrogen level in the red border area.…”
Section: Introductionmentioning
confidence: 99%
“…Even before the pandemic, practitioners, researchers, and governments had all been calling for supply chains to become more resilient and responsive to disruptions (see Ali & Gölgeci, 2019;Kaufmann et al, 2018). Taken together, the four articles in this issue, and previous works in JBL (see Gabler et al, 2017;Goldsby et al, 2019) and related journals (Ali & Gölgeci, 2019;Chowdhury et al, 2019;Ivanov, 2021;Kaufmann et al, 2018) build on an extensive base of research in the area of SCML resiliency and complexity, as both are central to the development of effective SCML strategy. Although the contexts may differ, resilience is also widely researched in other disciplines, so we hope to see more interdisciplinary perspectives that will continue to advance the field's understanding of this phenomenon.…”
Section: What Is Supply Chain Resilience?mentioning
confidence: 94%